An imaging mass spectrometry atlas of lipids in the human neurologically normal and Huntington's disease caudate nucleus. Issue 6 (8th March 2021) - Hunter, Mandana; Demarais, Nicholas J.; Faull, Richard L. M.; Grey, Angus C.; Curtis, Maurice A.
Abstract: Huntington's disease (HD) is a fatal disorder associated with germline trinucleotide repeat expansions in the HTT gene and characterised by striatal neurodegeneration. No efficacious interventions are available for HD, highlighting a major unmet medical need. The molecular mechanisms underlying HD are incompletely understood despite its monogenic aetiology. However, direct interactions between HTT and membrane lipids suggest that lipidomic perturbations may be implicated in the neuropathology of HD. In this study, we employed matrix‐assisted laser desorption/ionisation imaging mass spectrometry (MALDI–IMS) to generate a comprehensive, unbiased and spatially resolved lipidomic atlas of the caudate nucleus (CN) in human post‐mortem tissue from neurologically normal ( n = 10) and HD ( n = 13) subjects. Fourier transform‐ion cyclotron resonance mass spectrometry and liquid chromatography–tandem mass spectrometry were used for lipid assignment. Lipidomic specialisation was observed in the grey and white matter constituents of the CN and these features were highly conserved between subjects. While the majority of lipid species were highly conserved in HD, compared to age‐matched controls, CN specimens from HD cases in our cohort spanning a range of neuropathological grades showed a lower focal abundance of the neuroprotective docosahexaenoic and adrenic acids, several cardiolipins, the ganglioside GM1 and glycerophospholipids with long polyunsaturated fatty acyls. HD cases showed a higher focal abundance of several sphingomyelins and glycerophospholipids with shorter monosaturated fatty acyls. Moreover, we demonstrate that MALDI–IMS is tractable as a primary discovery modality comparing heterogeneous human brain tissue, provided that appropriate statistical approaches are adopted. Our findings support further investigation into the potential role of lipidomic aberrations in HD. Abstract : The caudate nucleus is the brain region most affected in the neurodegenerative disorder Huntington's disease. Lipid abnormalities are thought to contribute to the pathogenesis of this condition. In this study, matrix‐assisted laser desorption/ionisation (MALDI) imaging mass spectrometry coupled with Fourier transform and liquid chromatography mass spectrometry was used to create a lipidomic atlas of the caudate nucleus in post‐mortem tissue from Huntington's disease and matched neurologically normal subjects. Comparison of lipid profiles in disease and control tissue revealed focal differences in the abundance of multiple lipids within the caudate nucleus that may be relevant to the pathology in this region.